2011
DOI: 10.1007/s11524-011-9548-7
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Social Norms, Expectations, and Attitudes toward Corporal Punishment among an Urban Community Sample of Parents

Abstract: Despite the fact that corporal punishment (CP) is a significant risk factor for increased aggression in children, child physical abuse victimization, and other poor outcomes, approval of CP remains high in the United States. Having a positive attitude toward CP use is a strong and malleable predictor of CP use and, therefore, is an important potential target for reducing use of CP. The Theory of Planned Behavior suggests that parents' perceived injunctive and descriptive social norms and expectations regarding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
103
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(114 citation statements)
references
References 63 publications
2
103
0
1
Order By: Relevance
“…Since the early work on norms and students' use of alcohol, a large number of empirical studies investigated how discordant norms and attitudes influence people's practices "e.g. [28,29,[83][84][85][86][87][88][89][90][91][92]". Norms and attitudes, however, can be aligned: not only can people believe that compliance with a harmful practice is expected of them, they can also have a positive personal attitude towards that practice.…”
Section: Pitfall #2: Focussing Exclusively On Discordant Norms and Atmentioning
confidence: 99%
“…Since the early work on norms and students' use of alcohol, a large number of empirical studies investigated how discordant norms and attitudes influence people's practices "e.g. [28,29,[83][84][85][86][87][88][89][90][91][92]". Norms and attitudes, however, can be aligned: not only can people believe that compliance with a harmful practice is expected of them, they can also have a positive personal attitude towards that practice.…”
Section: Pitfall #2: Focussing Exclusively On Discordant Norms and Atmentioning
confidence: 99%
“…Attributing causation is complex. The declining approval of physical punishment is likely to be due to a combination of interconnected factors: extensive community action over decades; a general shift in values and norms on the acceptability of violence in society; increased awareness of children's rights; increased salience of childrearing practices due to parent education initiatives; public debate and media reporting of child abuse and law change itself 5 17 33 34…”
Section: Explaining the Change In Public Attitudesmentioning
confidence: 99%
“…In a telephone survey of 500 parents in an urban southern city, Taylor, Hamvas, Rice, Newman, and DeJong (2011) found that the strongest predictor of parents' positive attitude towards CP was their perception that the professional they were most likely to turn to for advice about child discipline approved of CP. Professionals parents were most likely to turn to for advice were pediatricians (48%), religious leaders (21%), and mental health professionals (18%) (Taylor et al, 2011). Parents who did not endorse the use of CP perceived their sources of advice to not support the use of CP.…”
Section: Introductionmentioning
confidence: 99%
“…Parents report that they listen to professionals, including pediatric health care providers, regarding child discipline (Taylor et al, 2011). However, in a telephone survey of the parents of 2068 children aged 4 to 35 months examining the use and predictors of discipline practices, Regalado, Sareen, Inkelas, Wissow, and Halfon (2004) found that more than half of the parents surveyed denied discussing discipline with their physician in a health care visit in the past year.…”
Section: Introductionmentioning
confidence: 99%